Unlocking the Potential of Papuan Red Fruit (Pandanus conoideus Lamk): A Comprehensive Exploration of Its Role in COVID-19 Inhibition Through Molecular Docking and Molecular Dynamics Simulation - Ananto, Agus Dwi; Pranowo, Harno Dwi; Haryadi, Winarto; Prasetyo, Niko (Indonesian Journal of Chemistry, 2025)
Indonesia's rich flora has long been used in traditional herbal medicine, and scientific research is now confirming the health benefits of these plants. Among them, Papuan Red Fruit is gaining attention for its potential in treating various ailments, including COVID-19, due to its antioxidant and antibacterial properties. This study focuses on using in silico methods to investigate how Papuan Red Fruit might inhibit COVID-19, specifically by targeting the papain-like protease (PLpro), a key protein in viral replication. Molecular docking and molecular dynamics (MD) simulations were used to assess the binding affinity and stability of compounds from the fruit. The compound quercetin 3'-glucoside showed the lowest binding energy, indicating strong interactions with PLpro. MD simulations at 300 K for 100 ns confirmed the stability of the quercetin 3'-glucoside-PLpro complex, revealing hydrogen bonds with residues like GLN169. The simulations showed an average delta RMSD of 0.2702 Å, indicating the complex's stability. Overall, this research highlights the potential of Papuan Red Fruit as a natural treatment for COVID-19, opening the door for further studies in drug development.